Program Design in Currency Unions. (Policy Papers; Policy Paper ;, 2018)
Despite a long history of program engagement, the Fund has not developed guidance on program design in members of currency unions. The Fund has engaged with members of the four currency unions-the Central African Economic and Monetary Community, the Eastern Caribbean Currency Union, the European Monetary Union, and the West African Economic and Monetary Union-under Fund-supported programs. In some cases, union-wide institutions supported their members in undertaking adjustment under Fund-supported programs. As such, several programs incorporated-on an ad hoc basis-critical policy actions that union members had delegated. Providing general guidance on program design for members in a currency union context would fill a gap in Fund policy and help ensure consistent, transparent, and evenhanded treatment across Fund-supported programs. This paper considers two options on when and how the Fund should seek policy assurances from union-level institutions in programs of currency union members. Option 1 would involve amending the Conditionality Guidelines, which would allow the use of standard conditionality tools with respect to actions by union-level institutions. Option 2-which staff prefers-proposes formalizing current practices and providing general guidance regarding principles and modalities on policy assurances from union-level institutions in support of members' adjustment programs. Neither option would infringe upon the independence (or legally-provided autonomy) of union-level institutions, since the institutions would decide what measures or policy actions to take-just as any independent central bank or monetary authority does, for example, in non-CU members.